2015
DOI: 10.1177/0091552115569847
|View full text |Cite
|
Sign up to set email alerts
|

Credentialing Structures, Pedagogies, Practices, and Curriculum Goals

Abstract: Objective: To examine the discursive strategies deployed by community colleges to sustain legitimacy in an evolving and contradictory institutional environment. Method: Using corpus linguistics software, I compared 1,009 mission statements from 2012-2013 with a reference corpus of 427 mission statements from 2004. Results: Keywords analysis, collocation analysis, and concordance analysis suggest that mission statements have changed along four discourse trajectories: credentialing structures, pedagogies, practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…First among these is the combination of shifts in practice norms and the development of new prestige-conferring fixtures in the postsecondary domain. Given their multiple and locally oriented missions, community colleges as a sector largely lack the sources of relative prestige (e.g., ranking, awards, selectivity) that incentivize the competition common among four-year colleges and universities (Ayers, 2015;Dowd, 2013). Funders not only created a public dialogue about data practice, but connected this dialogue to multiple types of incentives, including induction into valued networks, inclusion in high-profile prize competitions, and even consideration for future grant-funded projects.…”
Section: Naming Problematicmentioning
confidence: 99%
“…First among these is the combination of shifts in practice norms and the development of new prestige-conferring fixtures in the postsecondary domain. Given their multiple and locally oriented missions, community colleges as a sector largely lack the sources of relative prestige (e.g., ranking, awards, selectivity) that incentivize the competition common among four-year colleges and universities (Ayers, 2015;Dowd, 2013). Funders not only created a public dialogue about data practice, but connected this dialogue to multiple types of incentives, including induction into valued networks, inclusion in high-profile prize competitions, and even consideration for future grant-funded projects.…”
Section: Naming Problematicmentioning
confidence: 99%
“…Some recent empirical scholarship has explored community college degree-granting missions by analyzing institutions’ mission statements rather than looking at actual degree-granting behaviors (e.g., Abelman & Dalessandro, 2008; Ayers, 2005, 2011, 2015). Ayers (2005) found that community college mission statements adhered to neoliberal notions of curricular mission, emphasizing short-term vocational certificates that benefited statewide economic development goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This highlights a continued emphasis on short-term vocational degrees, somewhat in contrast to the increased emphasis on transfer cited above. Drawing on institutional theory, Ayers (2015) views mission statements as a means by which community colleges signal their allegiance to goals perceived as legitimate by important external resource providers (e.g., state policymakers, federal policymakers, and firms). He argued that community colleges rhetorically shifted in emphasis away from “occupational and vocational education” and toward “degree completion,” reflecting a growing policy consensus about the community college degree completion and transfer agenda (Ayers, 2015, p. 201).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…No longer an “aberrant practice” (Levin, Kater, & Wagoner, 2006, p. 18), this trend has added to decades of ongoing debates and discussions regarding the origin, purposes, missions, impacts, contradictions, and futures of the community college well documented in the literature (Ayers, 2005, 2009, 2015; Doughtery, 1994; R. A. Rhoades & Valadez, 2016).…”
mentioning
confidence: 99%